An Overview of Seasonal Changes in Oxidative Stress and Antioxidant Defence Parameters in Some Invertebrate and Vertebrate Species. (4th April 2016) - Chainy, Gagan Bihari Nityananda; Paital, Biswaranjan; Dandapat, Jagneswar
Abstract : Antioxidant defence system, a highly conserved biochemical mechanism, protects organisms from harmful effects of reactive oxygen species (ROS), a by-product of metabolism. Both invertebrates and vertebrates are unable to modify environmental physical factors such as photoperiod, temperature, salinity, humidity, oxygen content, and food availability as per their requirement. Therefore, they have evolved mechanisms to modulate their metabolic pathways to cope their physiology with changing environmental challenges for survival. Antioxidant defences are one of such biochemical mechanisms. At low concentration, ROS regulates several physiological processes, whereas at higher concentration they are toxic to organisms because they impair cellular functions by oxidizing biomolecules. Seasonal changes in antioxidant defences make species able to maintain their correct ROS titre to take various physiological functions such as hibernation, aestivation, migration, and reproduction against changing environmental physical parameters. In this paper, we have compiled information available in the literature on seasonal variation in antioxidant defence system in various species of invertebrates and vertebrates. The primary objective was to understand the relationship between varied biological phenomena seen in different animal species and conserved antioxidant defence system with respect to seasons.